Da’wah-Based Deradicalization: A Case Study of the Da’wah Cadre Training Program (PKD) Conducted by the PC LDNU of Tulungagung - Mohammad Khadziqun Nuha (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the implementation of the Da’wah Cadre Training Program (PKDNU) organized by the Branch Leadership of the Nahdlatul Ulama Da’wah Institution (PC LDNU) of Tulungagung as a strategy for countering radicalism. Radical ideology poses a serious threat to social cohesion and national unity by promoting exclusive religious interpretations that legitimize certain groups while delegitimizing others. In response to this challenge, this research employs a qualitative case study approach with a field research design. Data were collected through in-depth interviews with program organizers, instructors, and participants, participant observation during training activities and community da’wah implementation, as well as documentation analysis of curriculum guidelines and official program materials. The findings reveal that the PKDNU functions as a structured and systematic deradicalization initiative by strengthening moderate Islamic values rooted in Ahlussunnah wal Jama‘ah principles. The program equips da’wah cadres with inclusive theological understanding, adaptive preaching methodologies, and national civic awareness, enabling them to actively disseminate moderation values in both urban and remote areas of Tulungagung. Furthermore, the annual and continuous implementation of the program ensures the sustainability of moderate religious narratives at the grassroots level, thereby reinforcing community resilience against extremist ideologies. This study contributes to the academic discourse on community-based deradicalization by demonstrating that structured da’wah cadre training within Islamic civil society organizations can serve as an effective preventive model for countering radicalism beyond state-centered approaches.